Keeping the peace in the village conflict and peacemaking in Germany, 1650-1750 - Forster, Marc R. 1959- (Oxford University Press, 2024)
Keeping the Peace in the Village describes the nature of conflicts among rural people in the period after the Thirty Years' War. These included property disputes, conflicts between employers and their workers, disputes over marriage promises, and, most often, honor disputes
Keywords: Geschichte 1650-1750; Ländlicher Raum; Konfliktlösung; Deutschland; Early modern history: c 1450/1500 to c 1700; European history; Europäische Geschichte; HISTORY / Renaissance; HISTORY / Social History; Social & cultural history; Sozial- und Kulturgeschichte